Classroom Management Strategies To Enhance Learning Independence In Elementary School Students - Rifalda, Rifalda; Gagaramusu, Yusdin; Khairunnisa, Khairunnisa; Rizal, Rizal (FKIP - Universitas Riau, 2025)
This study aims to identify classroom management strategies and their implementation in enhancing the learning independence of fourth grade students at SD Inpres 1 Tanamodindi in the 2023/2024 academic year, located in Palu, Central Sulawesi. The research is based on the importance of learning independence as one of the key indicators of educational success in elementary schools, which requires teachers to have effective classroom management strategies tailored to students' characteristics. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation involving the principal, classroom teacher, and students. The findings indicate that teachers apply strategies such as flexible seating arrangements, assigning students responsibilities in learning activities, and creating a positive and conducive classroom atmosphere. The implementation of these strategies positively influences students’ learning independence, as reflected in their ability to manage study time, complete tasks independently, and show increased motivation and learning discipline. Thus, well-designed and effectively implemented classroom management contributes significantly to fostering students' learning independence at the elementary school level. In conclusion, appropriate classroom management strategies play a vital role in creating a learning environment that encourages students to become more independent, active, and responsible in their learning process.